MICROBIAL DECOLOURIZATION AND DEGRADATION OF CRYSTAL VIOLET BY AEROBIC BACTERIA - P. R. THORAT; M. SAYYAD (The Bioscan, 2010)
In present study, it was observed that, 92% decolourization of Crystal violet dye by the unidentified acclimatized bacterial cultures isolated from soil, collected from near by area of dye industry. The decolourization was achieved when dye solution was incubated at room temperature for 24 h. The decolourization was effective at neutral pH. No significant increase in decolourization was observed when the bacteria were supplemented with co-substrate (1% Glucose). Gas chromatography- mass spectroscopy analysis was carried out for confirmation of degradation. Five degradation products were isolated and identified.